Pengaruh Likuiditas dan Kesempatan Investasi serta Profitabilitas terhadap Keputusan Investasi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Mirna Wati; Maryam Nadir; Djoko Setyadi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
This study examines the influence of liquidity and invesment opportunity as well as profitability on the invesment decision of the manufacture companies listed in the Indonesia Stock Exchange from 2013 to 2015. The research aimed at testing the influence of liquidity and invesment opportunity as well as profitability on the invesment decision. The sample included 37 companies by using the purposive sampling method. The analysis technique employed in this research was the multiple linier regression analysis. The result of study show the liquidity had a postive significant influence on the invesment decision, the invesment opportunity had a positive and significant influence on the invesment decision and profitability also had a positive significant influence on the invesment decision.Keyword: Invesment decision, invesment opportunity, liquidity, profitability